Children with cerebral palsy: why are they awake at night? A pilot study. Issue 2 (29th January 2015) - Petersen, Sacha; Harvey, Adrienne; Reddihough, Dinah; Newall, Fiona
Abstract Purpose The purpose of this study was to assess acceptability of study design and utility of assessment tools for determining causes of sleep disturbance in children with cerebral palsy (CP) and their caregivers. Design and Methods This pilot study explored parental report (n = 8) of the child's sleep using a validated sleep questionnaire, a survey, and a time use diary. Results The selected tools were appropriate. Study design provided challenges for recruitment. Future research should include qualitative data. Practice Implications Although further research is required to confirm results, sleep problems for children with CP and resulting sleep disturbances for caregivers may be an important part of clinical assessment.